Analysis of Electoral Geography in West Azerbaijan Province (apportionment, Gerrymandering) - ZAHRA PISHGAHI FARD; keramat ranjbar dastenaei (نشریه جغرافیا و برنامه‌ریزی, 2021)
Introduction Geography explains the man-environment relationships and the geographical environments and spaces need the political organization of space is needed for optimal governance. It is impossible or it will be accompanied by many difficulties to manage space without political management and to define clear boundaries by dividing space into local, national and regional dimensions. Thus, political geography examines the effect of political decisions on the environment and geographical space and human relations. If sovereignty arises from the nation, political decisions have acceptability and legitimacy. In this geographical debate, elections as a branch of political geography examine the proportionality or disproportion of electoral areas' seats to the population, as well as the manipulation of electoral areas' boundaries (Gerrymandering) that leads to the continued victory of a person or political faction. The Islamic Consultative Assembly is considered as the main and most important decision-making element in the Islamic Republic of Iran, which periods have passed since the beginning of the Islamic Revolution, and according to the existing laws (Article 64 of the Constitution), each area can change according to decreasing or increasing the number of members of parliament in each ten-year period and the geographical boundaries, which necessarily leads to changes in the boundaries of the electoral area and manipulation of the boundaries, in the meantime, the examination of voting patterns and voting and ballots can manipulate and change boundaries in favor of one person or party, and lead to continued victory in electoral areas. On the other hand, if there is a mismatch between these manipulations with the proportion of the population and electoral seats call into question spatial justice and democracy, so political geographers, especially election geographers, examine these issues and analyze electoral areas Materials and methods In the present study, the dispersion and deviation from the criteria and division of electoral areas has been investigated using library resources, approvals of the Islamic Consultative Assembly, Statistics Center of Iran, field observation, interviews with representatives and using Spss v22 software, as well as electoral areas maps in different periods are examined using the GIS software geographic information system, and the maps of each electoral area are drawn before and after the changes, and based on one or more of six methods, Gerrymandering is discovered as follows.